Pengukuran Kinerja Green Supply Chain Management (GSCM) Menggunakan OMAX dan Pendekatan PDCA pada PT. Putra Multi Cipta Teknikindo - Kent F. R. Temenggung Zees; Cyrilla Indri Parwati; Andrean Emaputra (Universitas Sarjanawiyata Tamansiswa, 2022)
In industrial sector activities, supply chain processes involve extracting and exploiting natural resources that may hurt the environment. Based on this, an approach to supply chains that is more environmentally friendly is needed. Green supply chain management (GSCM) integrates environmental thinking into supply chain management, including product design, material sourcing and selection, manufacturing processes, final delivery of products to consumers, and end-of-life management after the last utilization period. PT. Putra Multi Cipta Teknikindo is a company engaged in the trade of goods and services. Trade in goods and services includes batik stoves, small industrial production machines, industrial and laboratory scale measuring and detection equipment, and batik workshops. The purpose of this study is to measure the performance of GSCM in PT. PMC Teknikindo. This research is expected to provide information on the company's performance conditions in applying GSCM. The company is expected to be responsive to this performance measurement to increase the performance of related indicators so that there is continuous improvement. GSCM performance measurement uses the Plan, Do, Check, Action (PDCA) approach with Analytical Network Process (ANP), Objective Matrix (OMAX), and Traffic Light System (TSL) methods. The results of this study are the total KPI value of 4,867 which means the GSCM performance of PT. PMC Teknikindo has not reached the target. The results of the performance measurement indicators contained 26 KPIs in the yellow category, 5 KPIs in the red category, and 1 KPI in the green category. Based on these results, it is necessary to recommend improvements to related indicators to optimize achievement.